The moderating effect of a firm's internal climate for innovation on the impact of public R&D support programmes. (24th February 2004) - Wong, Poh-Kam; He, Zi-Lin
This study investigates the influence of a firm's internal climate for innovation on the relationship between public R&D support and the innovation behaviour of the firm. We hypothesise that, if there is a positive relationship between public R&D support and a firm's innovation activities, this phenomenon is more likely to be observed in firms with an internal climate that promotes innovation, rather than in firms with a restrictive one. Based on a sample of 135 manufacturing firms in Singapore, we discover the significant moderating effect of a firm's internal climate for innovation on the impact of public R&D support on several measures of a firm's innovation input, output and collaboration behaviour. We identify two distinct dimensions of internal climate for innovation (organisational policies and individual attitudes), which exhibit different moderating effects.